School Heads’ Direct Supervision, Attitudes and Practices and Teachers’ Performance during the Post Pandemic Era - Tuico, Edgar V.; Callo, Elsa C. (Future Science / FSH-PH Publications, 2024)
This study investigated the impact of school leaders' direct supervision, attitudes, and practices on teachers' performance in the post-pandemic era. This study used a quantitative method with a predictive design involving 350 permanent teachers from SDO San Pablo City's four (4) large public junior high schools for the school year 2022-2023. A survey questionnaire was used to assess the level of direct supervision provided by school heads in terms of lesson planning and delivery; the level of attitudes provided by school heads in terms of motivation, communication, respect, decision-making, and sensitivity; and the level of practices provided by school heads in terms of teachers' support during the transition period; meeting needs; maintaining communication contact and relationship; celebrating success; and maintaining quality. Using the mean and standard deviation, it was discovered that respondents' level of agreement to school heads' direct supervision in all instructional processes is very high; respondents' level of agreement to school heads' attitudes in terms of motivation, communication, and respect is also very high; respondents' level of agreement to school heads' practices in all sub-variables is also very high; and respondents' level of agreement to their performance is also very high. School leaders' direct supervision, attitudes, and practices are significantly related to teachers' performance. Likewise, teachers' performance significantly predicted school heads' practices in maintaining communication contact and relationship, as well as school heads' direct supervision in lesson planning As a result, it may be recommended that school leaders continue to direct the three (3) instructional processes to improve teaching, develop more positive attitudes to boost teacher morale, and maintain school practices, as teachers require more support in this post-pandemic era.